2017
DOI: 10.1177/0300060517734460
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine protects against oxygen-glucose deprivation/reoxygenation injury-induced apoptosis via the p38 MAPK/ERK signalling pathway

Abstract: ObjectiveTo investigate the protective effects of dexmedetomidine (DEX) in oxygen-glucose deprivation/reoxygenation (OGD/R) injury, which is involved in a number of ischaemic diseases.MethodsAn in vitro OGD/R injury model was generated using mouse Neuro 2A neuroblastoma (N2A) cells. Different concentrations of DEX were administrated to OGD/R cells. CV-65 was used to inhibit p38 microtubule associated protein kinase/extracellular signal-regulated kinases (MAPK/ERK) signalling. Cell proliferation, cell cycle, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 32 publications
(39 reference statements)
1
16
1
Order By: Relevance
“…For instance, Bonney EA t et al 52 reported attenuated ischaemia-reperfusion injury mediated by inhibition of the p38MAPK signalling pathway. Wang et al 28 also illustrated the effect of DEX in altering oxygen deprivation/reoxygenation-induced apoptosis via the p38MAPK signalling pathway in N2A cells. In this study, Figure 7 The effects of dexmedetomidine on the expression of GRP78, CHOP and caspase-12 in myocardial cells treated under different conditions were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Bonney EA t et al 52 reported attenuated ischaemia-reperfusion injury mediated by inhibition of the p38MAPK signalling pathway. Wang et al 28 also illustrated the effect of DEX in altering oxygen deprivation/reoxygenation-induced apoptosis via the p38MAPK signalling pathway in N2A cells. In this study, Figure 7 The effects of dexmedetomidine on the expression of GRP78, CHOP and caspase-12 in myocardial cells treated under different conditions were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that DEX has a protective effect on kidney injury [ 29 ]. In addition, DEX has been shown to inhibit the release of proinflammatory cytokines [ 30 , 31 ], attenuate apoptosis [ 32 , 33 ], and reduce ROS production [ 34 , 35 ]. However, protective roles of DEX during acute stress-induced kidney injury are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have demonstrated that DEX stabilizes perioperative stress-induced hyperglycemia and decreases IR in patients with diabetes; this may be related to a reduction in sympathetic activity, analgesia, and antiinflammatory response [13]. DEX exerted protective effects in lungs by reducing the levels of ERS in a model of ischemia-reperfusion injury [35], and was shown to be closely related to ERS caused by burns and glucose deprivation [12,14,16]. However, the effects of DEX on ERS in an IR model have not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Medium containing 10% CCK-8 reagent was added to the well, followed by incubation for 1-3 h at 37Ā°C. When the color of the medium turned dark orange, optical density at 450 nm (OD 450 ) was measured and a standard curve of cell viability was generated [16].…”
Section: Cell Viability Assaymentioning
confidence: 99%